2016
DOI: 10.1111/tpj.13191
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 canonical content organizes a molecular scaffold mechanism to progress flowering

Abstract: SUMMARYHighly interactive signaling processes constitute a set of parameters intertwining in a continuum mode to shape body formation and development. A sophisticated gene network is required to integrate environmental and endogenous cues in order to modulate flowering. However, the molecular mechanisms that coordinate the circuitries of flowering genes remain unclear. Here using complemented experimental approaches, we uncover the decisive and essential role of HEAT SHOCK PROTEIN 90 (HSP90) in restraining dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 56 publications
0
36
1
Order By: Relevance
“…After synthesis in the ribosome, the polypeptide chain rapidly folds into its characteristic and functional three-dimensional structure from a random coil. This process is accomplished through the assistance of chaperones, such as the ER-resident molecular chaperone BiP, the HSP70 family, and the HSP90 family 5055 . The data in the present study showed that lysine residues in members of HSP70 and HSP90 were extensively crotonylated in tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…After synthesis in the ribosome, the polypeptide chain rapidly folds into its characteristic and functional three-dimensional structure from a random coil. This process is accomplished through the assistance of chaperones, such as the ER-resident molecular chaperone BiP, the HSP70 family, and the HSP90 family 5055 . The data in the present study showed that lysine residues in members of HSP70 and HSP90 were extensively crotonylated in tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis , HSP90, as a molecular chaperone, contributes to BR-mediated gene expression through complex formation with two major TFs, BZR1 and BES1 (Samakovli et al, 2014; Shigeta et al, 2015). A recent study reported that HSP90 is pivotal in the transition from vegetative to reproductive phase in Arabidopsis and that depletion of HSP90 mRNA levels causes extreme variation in the expression of flowering genes, and disturbs flower determination and patterning (Margaritopoulou et al, 2016). We found that a large number of HSP genes were regulated by BR treatment, indicating that HSPs also have a central function in BR-regulated petal growth in G. hybrida.…”
Section: Discussionmentioning
confidence: 99%
“…In Ipomoea nil (formely Pharbitis nil, the Japanese morning glory), hsp83 was upregulated upon exposure to a photoperiod that induces flowering (Felsheim and Das, 1992). The heat shock protein Hsp90 was also reported to act as an environmental signal sensor regulating flowering time (Sangster et al, 2007) and flower development (Margaritopoulou et al, 2016). Another missense variant was found at a gene encoding for a protein kinase U-box domain-containing.…”
Section: Biological Insights Into the Genetic Basis Of Fruit-related mentioning
confidence: 99%